Strategic approach for achieving high indoor efficiency of perovskite solar Cells: Frustration of charge recombination by dipole induced homogeneous charge distribution - Choi, Min Jun; Lee, Seok Woo; Lee, Minwoo; Shin, So Jeong; Kim, Moonyong; Jeon, Gyeong G.; Yoon, Sang Eun; Xiangyang, Fan; Lee, Bo Ram; Seidel, Jan; Yun, Jae Sung; Chang, Dong Wook; et al. (Chemical Engineering Journal, 2023)
Indoor-light harvesting-technology based on perovskite solar cells have attracted significant attention owing to their promising photovoltaic properties as indoor power generators. We investigated the effect of interfacial dipoles on the performance of perovskite solar cells in low-intensity indoor light environments. Interfacial dipoles were controlled by inserting different polar layers with different molecular dipole moments (BCP, QPPO and QDPPO) on top of electron transport layers (ETLs). Significantly improved uniformity of interfacial dipoles, in the QDPPO layer, effectively reduced charge recombination and enabled persistent fill factors (FF's) under low-intensity light environments. Perovskite solar cells based on QDPPO exhibited indoor power density (iPD) and indoor power conversion efficiency (iPCE) of 65.63 μW/cm2 and 27.49 % under 800 lux LED, which were further enhanced up to 88.09 μW/cm2 and 36.90 % by employing additional passivation layer under 800 lux LED. Finally, using QDPPO, we successfully demonstrated perovskite photovoltaic mini-modules with a high power output of 2.4 mW under a 1,000 lux halogen, which can be applied in Internet-of-Things sensors under indoor light conditions.
Keywords: Charge recombinations; Indoor light; Indoor photovoltaic; Interface dipole; Interface dipole layer; Interfacial dipoles; Low-intensity; Mini-module; Photovoltaics; Recombination; Indoor photovoltaics; Interface dipole layers; Mini-modules; Perovskite solar cells; Recombination